SKEPTISISME TEOLOGIS DAN JAWABAN FILSAFAT - Norbertus Jegalus (UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2012)
Human language deals with sense experience. When human language has to speak on God, there comes the problem on which experience man can talk about Him. For God does not deal with human sense experience. How is it possible to use human language which is limited to his sense experience, to speak on God without lowering Him on human level? It precisely is the possibility of analogy. Analogy makes human language remain limited to his dimensional life and, at the same time, gives the possibility to speak on and talk with God. For essentially human being is spiritual and his language by his reason and the will contains human capacity to reach God.